(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
In this article, we demonstrates how to make stronger the encrypted message being sent by use of ElGamal so only the proposed receiver of the message is efficient to decode the message. Our result is also illustrated with help of an mathematical example with calculation. We also show that our proposed scheme process faster than RSA scheme.